Inovasi UMKM Lokal Dalam Pengembangan Produk Kue Tradisional Aceh Di Era Modern: Studi Pada Toko Kue Inabah - Yusnita, Yusnita (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the innovation of local Micro, Small, and Medium Enterprises (MSMEs) in developing traditional Acehnese cakes in the modern era, using Toko Kue Inabah as a case study. Located in Langung Village, Aceh Barat, Inabah has emerged as a traditional cake producer that successfully integrates cultural heritage with modern business practices. This research aims to explore the history of the business, product diversification, innovation strategies, and the socio-economic impacts of the enterprise on the surrounding community. The study employs a qualitative descriptive approach, with data collected through observation and interviews with the business owner and local workers. The findings reveal that Toko Kue Inabah preserves traditional culinary values while implementing innovations such as modern packaging, improved hygiene standards, and product consistency. Additionally, collaboration with local home-based producers particularly women has strengthened community empowerment and contributed to increased household income. This study concludes that Inabah serves as a model of MSME development that synergizes economic sustainability and cultural preservation. Further research is recommended to explore digital marketing strategies and consumer behavior toward traditional culinary products.